COVID‐19 vaccination in haematology patients: an Australian and New Zealand consensus position statement. Issue 5 (27th May 2021) - McCaughan, Georgia; Di Ciaccio, Pietro; Ananda‐Rajah, Michelle; Gilroy, Nicole; MacIntyre, Raina; Teh, Benjamin; Weinkove, Robert; Curnow, Jennifer; Szer, Jeff; Enjeti, Anoop K; Ross, David M; Mulligan, Stephen; et al.
Abstract : Australia and New Zealand have achieved excellent community control of COVID‐19 infection. In light of the imminent COVID‐19 vaccination roll out in both countries, representatives from the Haematology Society of Australia and New Zealand and infectious diseases specialists have collaborated on this consensus position statement regarding COVID‐19 vaccination in patients with haematological disorders. It is our recommendation that patients with haematological malignancies, and some benign haematological disorders, should have expedited access to high‐efficacy COVID‐19 vaccines, given that these patients are at high risk of morbidity and mortality from COVID‐19 infection. Vaccination should not replace other public health measures in these patients, given that the effectiveness of COVID‐19 vaccination, specifically in patients with haematological malignancies, is not known. Given the limited available data, prospective collection of safety and efficacy data of COVID‐19 vaccination in this patient group is a priority.